Utilization of Ovary Collected from Abattoir as Genetic Material Resources - Arie Febretrisiana; Fitra Aji Pamungkas (Indonesian Center for Animal Research and Development, 2017)
Slaughtering productive cow is commonly practiced, eventhough it is not in accordance with government program to increase livestock population in Indonesia. Ovarium from slaughtered cow contains genetic materials that have not utilized properly. The purpose of this paper is to review ovarian utilization collected from abattoir through in vitro fertilization technology. The best procedure of ovary preservation from abbatoir to the laboratory, oocyte collection techniques are required to produce qualified embryo. Transportation of ovary to laboratory requires proper temperature and time. Slicing method obtains high quantity and good quality of oocyte. The quality of oocytes collected from abattoir as good as those taken from live animal. Ovaries that previously as waste product can be used for in vitro production of embryos and livestock genetic material resources.